1988
DOI: 10.1002/ana.410240113
|View full text |Cite
|
Sign up to set email alerts
|

A treatable multifocal motor neuropathy with antibodies to GM1 ganglioside

Abstract: We report 2 patients with a treatable, immune-mediated motor polyneuropathy associated with antibodies to defined neural antigens. In these patients asymmetrical weakness developed in one arm and progressed over 2 to 3 years to involve the other arm, legs, and trunk. Both patients were initially diagnosed as having lower motor neuron forms of amyotrophic lateral sclerosis. However, repeated electrophysiological testing eventually showed multifocal conduction blocks in motor but not sensory fibers compatible wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
305
3
15

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 585 publications
(331 citation statements)
references
References 28 publications
8
305
3
15
Order By: Relevance
“…This is important as different neuropathies may require specific therapeutic strategies (Nobile‐Orazio, 2014; Pestronk et al., 1988; van Schaik, van den Berg, de Haan, & Vermeulen, 2005). Comparative studies of brachial plexus MRI have not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…This is important as different neuropathies may require specific therapeutic strategies (Nobile‐Orazio, 2014; Pestronk et al., 1988; van Schaik, van den Berg, de Haan, & Vermeulen, 2005). Comparative studies of brachial plexus MRI have not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Parry and Clarke 29 (and in a separate report, Pestronk et al 30 ), reported similar patients. Since then, there have been a number of studies describing patients who have multifocal motor neuropathy (MMN) with persistent conduction block.…”
Section: Multifocal Motor Neuropathymentioning
confidence: 78%
“…However, several relevant autoantibodies in nonparaneoplastic inflammatory neuropathies are of the IgM isotype. This includes anti‐MAG antibodies associated to monoclonal gammopathy of unknown significance and plasma cell dyscrasias,30 anti‐GM1 antibodies in multifocal motor neuropathy31, and anti‐disialosyl antibodies in CANOMAD syndrome 32. Four out of 10 patients with sensory‐motor neuropathy stained Schwann cells.…”
Section: Discussionmentioning
confidence: 99%